2016
DOI: 10.2139/ssrn.2717988
|View full text |Cite
|
Sign up to set email alerts
|

The Old Boy Network: The Impact of Professional Networks on Remuneration in Top Executive Jobs

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
(19 reference statements)
1
20
0
Order By: Relevance
“…We also use in the analysis another network-related variable, called 'Placebo connections', which measures the number of members of the BoardEx main database with whom an individual in our dataset has worked in the same firm but not at the same time. This is the same measure as developed in Lalanne and Seabright (2016) and (independently) in Hensvik and Skans (2016). This variable captures the various characteristics that individuals share with their contacts through being hired by the same employer, except for the fact of having been employed at the same time.…”
Section: Dataset and Empirical Strategymentioning
confidence: 99%
“…We also use in the analysis another network-related variable, called 'Placebo connections', which measures the number of members of the BoardEx main database with whom an individual in our dataset has worked in the same firm but not at the same time. This is the same measure as developed in Lalanne and Seabright (2016) and (independently) in Hensvik and Skans (2016). This variable captures the various characteristics that individuals share with their contacts through being hired by the same employer, except for the fact of having been employed at the same time.…”
Section: Dataset and Empirical Strategymentioning
confidence: 99%
“…A rich case study literature suggests that women tend to have smaller social networks than men and that women's networks feature more strong links and fewer weak links (Booth 1972;Moore 1990;Benenson 1993;Baumeister and Sommer 1997). Moreover, recent evidence supports the view that women and men leverage their networks differently (Mengel 2016;Beaman et al 2015) and obtain different work-related benefits because of different network structures (Lindenlaub and Prummer 2015;Lalanne and Seabright 2016). Differences in men's and women's social networks may therefore be key in understanding gender differences in career outcomes and may complement existing explanations of the persistent gender gap in labor market outcomes (see Bertrand (2011) for a recent survey).…”
Section: Introductionmentioning
confidence: 96%
“…In this case, however, while there is an absence of experimental evidence on global hiring practices, there is documentation of consistent trends in observational data in contexts much different than Malawi. For example, Lalanne and Seabright (2011) find that women executives in the U.S. and Europe don't leverage their contacts into higher salaries as well as their male counterparts. Loury (2006) using the NLSY found that male workers referred by women get lower on average wages than those who applied through formal channels.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently,Lalanne and Seabright (2011) find that male executives in the US and Europe have salaries which increase in numbers of executive contacts, while female executives do not receive this benefit.…”
mentioning
confidence: 99%